Mentoring Model For Technopreneurship Through Neurocoaching To Grow Up Technopreneurship Intention Of Students At Muria Kudus University - Supriyati, Endang; Iqbal, Mohammad; Khotimah, Tutik (IJTB (International Journal of Technology And Business), 2017)
DP2M DIKTI (the Indonesian Ministry of Research and Technology) launches 2 programs to grow up entrepreneurship intention. These programs are PKM( creativity student program) and PMW (entrepreneurship student program). Strategy of these programs produces job provider oriented graduates form university. The problem in the program , technoreneurship intention is not running well, because of activity student in the campus. As the result, the studentâs bussines and the character of techopreneurship is not grow up. The purpose of this paper is to analyze the impacts some factors on technopreneurship intention of university student. In the study, a model proposes and empirically tested on a sample of 221 students in Muria Kudus University â Central Java. Data were analyzed using SEM(Structural Equation Model) and SWOT. Neurocoaching method used for mentoring the program. Mentoring model devides of four step. First step : review about student bussines, second step : mentoring using neurocoaching method, third step: challenge, forth step : competition program technopreneurship among tenant. Neurocoaching is a fusion of neuroscience and neuro-linguistic programming (NLP) for the purpose of coaching people to excellence. The findings show that, Identity in the prediction of Intention is significantly, Environment in the prediction of Intention is significantly, for Believe in the prediction of Intention is significantly and Capability in the prediction of Intention is not significantly.